The effect of green marketing on purchase decisions in ecaps - Putra, Rezky Pujangga; Djunaid, Ika Suryono (Gema Wiralodra, 2023)
This study aims to examine the influence of green marketing on purchasing decisions at Ecaps. The research sample consists of 100 randomly selected Ecaps customers. The data used in this study includes both primary and secondary data, with the primary data collected through a validated and reliable questionnaire. The data analysis methods include simple regression, F-test, T-test, determination coefficient (R2), and correlation coefficient. The findings of this study indicate that the green product dimension does not have a significant positive impact on purchasing decisions at Ecaps. However, the green advertising and green brand dimensions have a significant favorable influence on purchasing decisions at Ecaps. The determination coefficient (R2) indicates that the variables in the research model explain approximately 44,1% of the variation in purchasing decisions. At the same time, the remaining variation is influenced by other unexplored factors. The data analysis was conducted using SPSS version 29 software. The main finding of this research highlights the importance of green marketing in influencing purchasing decisions at Ecaps. This study provides valuable insights for Ecaps in developing marketing strategies focusing on environmental aspects to enhance consumer purchasing decisions. As recommendations, the company must prioritize the development of environmentally friendly and sustainable products to create added value for consumers. Additionally, implementing advertising strategies aligned with sustainability values and building a strong brand image as an environmentally conscious company is essential. The company may also consider developing environmental-focused corporate social responsibility programs and promoting them to enhance purchasing decisions.